Frequency of Rickets in Patients Presenting with Lower Respiratory Tract Infection in Paediatric Unit of Ayub Teaching Hospital - Bibi, Nabila; Najeeb, Shahzad; Khan, Salman; Khalid, Maria (Indus Journal of Bioscience Research, 2025)
Background: Rickets is a significant concern in children with lower respiratory tract infections, especially among those from low socioeconomic backgrounds. This study aimed to assess the prevalence of rickets in pediatric patients diagnosed with LRTIs and examine its association with demographic factors, disease duration, and serum biochemical markers. Objective: To determine the frequency of rickets in patients presenting with lower respiratory tract infection in Pediatric Unit of Ayub Teaching Hospital, Abbottabad. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from June 2024 to December 2024 at the Pediatric Medicine Department of MTI-Ayub Teaching Hospital, Abbottabad. Methodology: A total of 189 patients aged 2 to 60 months, diagnosed with LRTIs, were enrolled. Data was collected through comprehensive medical histories, physical examinations, and biochemical tests measuring serum calcium, phosphorus, and alkaline phosphatase levels. Radiographic evidence of rickets was assessed using wrist X-rays. Results: Of the 189 children, 63.5% were diagnosed with rickets. The mean age was 28.37 ± 15.55 months, with a higher prevalence in children younger than 24 months (100%). Males exhibited a higher rate of rickets (87%) compared to females (37.1%), and 95.9% of children with symptoms lasting more than seven days had rickets. The prevalence was highest among children from low socioeconomic backgrounds (100%) and urban residents (92.2%). Conclusion: Our study shows a high prevalence of nutritional rickets in children with lower respiratory infections, especially those with chronic illness and low socioeconomic status. Vitamin D deficiency plays a key role, emphasizing early detection, supplementation, and screening in high-risk children.